Token Female Voice Enactment in Traditionally Male-Dominated Teams: Facilitating Conditions and Consequences for Performance - Farh, Crystal I. C.; Oh, Jo K.; Hollenbeck, John R.; Yu, Andrew; Lee, Stephanie M.; King, Danielle D. (Academy of Management Journal, 2020)
When is a token female’s voice incorporated into the actions of a traditionally male-dominated team, and to what ends? Drawing from the tokenism, gender stereotypes, and minority influence literatures, we advance a model that specifies the conditions that facilitate token female voice enactment and when enacting the female’s voice enhances team performance. Using a sample of active-duty military men and women, we employed live observation techniques to study voice enactment in all-male teams versus female-token teams (i.e., teams with a token female member) throughout a series of complex and physically demanding tasks. Our findings revealed that (a) token female voice enactment was higher when team leaders possessed more favorable beliefs about women’s capabilities in the military, and (b) token female voice enactment enhanced team performance in more complex tasks but harmed team performance in less complex tasks. Additionally, our supplementary analyses revealed that female-token teams were more reflective before engaging in action relative to all-male teams, as the latter tended to engage in agentic, “action-first” strategies. Theoretical and practical implications for facilitating female voice enactment in traditionally male-dominated contexts are discussed.